Educação ambiental na escola do campo : possibilidades e limites para com o rompimento da linha segregadora que torna a escola alheia à vida do campo - Silva, Maria Niely de Freitas (2017)
This research was developed within the framework of the program of postgraduate education of the Federal University of Mato Grosso, of the Institute of Humanities and social sciences, Campus Universitário de Rondonópolis (PPGEdu/UFMT/ICHS/CUR). Is an analysis about the possibilities and limits of Environmental Education actions to break the segregating line that makes the school remote to thecountry life, instituted by the More Education Program (PMEd), in the year of 2015, by two country schools in the Southeast Region of Mato Grosso. In order to support the theoretical discussions aboutCountry Education (CE) and Environmental Education (EE), it´s used authors such as Carlos Loureiro (2011), Enrique Leff (2013), Isabel Carvalho (2012), Lindalva Garske (2006), Mauro Guimarães (2011), Miguel Arroyo (2009), Mônica Molina (2010a), Michèle Sato (2003), Paulo Freire (2005), Philippe Layrargues (2012) and Roseli Caldart (2008). The methodological path was constructed based on the presuppositions of the qualitative research, in a dialectical perspective. Six people were interviewed, such as the principals and coordinators of the PMEd of the two schools analysed, one pedagogical coordinator and one monitor of the Program. As strategies and instruments of data collection, it has used: documentary analysis and semi-organized interviews. The result of the research evidenced possibilities and limits for the contribution of Environmental Education activities to the rupture of the segregating line that makes the school remote to the country life. The possibilities are established in the fact that the activities are presented as proposals aimed to the construction of social values, knowledge and skills that promote socioenvironmental sustainability and quality of life. On the other hand, the organization of a collective and dialogical work, which is a principle that guides Environmental Education activities aimed to the transformation of a certain socio-environmental reality, it´s shown up as a limit in the implementation of such activities. Another important limiting factor was the nonexistence of a training educators policy to work with EE activities.